Six-minute walk work in patients with chronic obstructive pulmonary disease - Dogra, Archana C.; Gupta, Urmil; Sarkar, Malay; Padam, Anita; Chauhan, Arun; Thakur, Smitacharu (International Journal of Research in Medical Sciences, 2017)
Background:Six Minute Walk Test (6MWT) has demonstrated good reliability and validity as an assessment for exercise tolerance for moderate to severe COPD. 6MWD is a known to be a preferred outcome for this test; however, it does not account for differences in body weight that are known to influence exercise capacity.Aim of current study was to correlate of distance product (6MWWORK) with various variables in study group of patients with Chronic Obstructive Pulmonary Disease (COPD). Methods:Sixty patients of diagnosed COPD underwent pulmonary function test and 6MWT. Correlation coefficients were calculated for the 6-Min Walk Distance (6MWD) and 6MWORK with variables of pulmonary function and 6MWT. Results:The mean of 6MWD was 312.0 ± 21.2 meters and mean 6MWWORK was 31246 ± 2414 kg.m in the study population. 6MWD significantly correlated with age (r = 0.25), height (r = 0.42), body mass index (r = -0.32) and body weight (r = 0.48). 6MWORK yielded higher correlation coefficients than did 6MWD when correlated with FEV (r = 0.66 vs. 0.35), FEV1/FVC ratio (-0.46 vs. -0.24). The ROC curve demonstrated that 6MWORK had a significantly larger calculated area under the curve (P <0.05) than 6MWD with FEV1. Conclusion: 6MWWORK is an improved outcome of 6MWT to monitor functional capacity in patients of chronic obstructive pulmonary disease.